EFFECT OF PROCESS PARMAETRS DURING FORMING OF SELF REINFORCED – PP BASED FIBER METAL LAMINATE - Sivakumar, Dhar Malingam (2012)
This research presents results on the stamp forming behavior of Fiber Metal Laminate Systems. A Design of Experiments approach was undertaken to elucidate the major effects of the process parameters that include blank holder force and temperature. Evolution of major strain and strain ratio were used as metrics in the analysis. A significant finding from this work is the identification of recrystallization behavior that significantly changed the forming behavior of this class of material systems.